2014
DOI: 10.1002/uog.12552
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of first‐trimester fetal abdominal cysts: cohort study and review of the literature

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Obviously, a cystic mass in the fetal abdomen prompts differential diagnosis with conditions other than ARA. Khalil et al, in a cohort retrospective study on 14 fetuses in which cystic structures were found at the first trimester anomaly scan, did not report any ARA but concluded that, considering the high probability that obstruction and gut malrotation produce bowel dilatation, this diagnosis should be included in differential diagnosis algorithms [24].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, a cystic mass in the fetal abdomen prompts differential diagnosis with conditions other than ARA. Khalil et al, in a cohort retrospective study on 14 fetuses in which cystic structures were found at the first trimester anomaly scan, did not report any ARA but concluded that, considering the high probability that obstruction and gut malrotation produce bowel dilatation, this diagnosis should be included in differential diagnosis algorithms [24].…”
Section: Discussionmentioning
confidence: 99%
“…There are nine additional reports in the literature on 14 cases of first trimester expression of ARM-including the present report (Table 1). [7][8][9][10][11][12][13][14][15] At least seven cases were terminated between 12 and 23 weeks, one case had late missed abortion at 18 W and two other cases were delivered at 29 and 39 weeks by cesarean section. At least nine cases had major associated anomalies, and three of these were on the VACTERL spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…In the present report, we describe a case of isolated ARM and its progression from the first trimester. In addition, we review the literature of all reported cases of first trimester sonographic expression of ARM (Table ) . For this purpose, we applied a systematic search in PubMed, Web of Science and SCOPUS to identify relevant citations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A recent review assessing the natural history of abdominal cysts diagnosed exclusively during the first trimester of pregnancy reported an overall good perinatal outcome for the majority of these lesions with high rates of pre or post-natal resolution. 4 However, prenatal counselling when an abdominal cyst is diagnosed during the second or third trimester of pregnancy is challenging; the evidence is sparse and mainly derived from small series. This is important as counselling for parents based on small studies that are subject to publication bias may be inadequate.…”
Section: Introductionmentioning
confidence: 99%